Asuhan Keperawatan Jiwa pada Klien dengan Halusinasi Pendengaran di Wisma Melati Rumah Sakit Jiwa Prof HB Saanin Padang - Alya Amelia Putri; Vivi Yuderna; Ramaita .; Dwi Happy Anggia Sari (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Hallucinations are sensory perception disturbances that occur without any real stimulus. One common type of hallucination is auditory hallucinations, which involve the perception of hearing voices or sounds that do not originate from external stimuli. Based on medical records at Prof. HB. Saanin Mental Hospital, Padang, the most common nursing problem in the past three years was hallucinations, with 12,419 patients. The purpose of this case study is to apply psychiatric nursing care to a client with auditory hallucinations at Prof. HB Saanin Mental Hospital, Padang. The method used in this scientific paper is a case study through a nursing process approach, which includes assessment, diagnosis, intervention, implementation, and evaluation. The assessment results indicate that the client experienced signs and symptoms of hallucinations, including hearing whispers. The primary diagnosis was hallucinations, with a co-diagnosis of self-care deficit. After providing this nursing care, the patient was able to independently control the hallucinations using implementation strategies (SP): SP 1: reprimanding, SP 2: taking medication regularly, SP 3: having conversations, and SP 4: carrying out scheduled daily activities. These results indicate that the implementation of implementation strategies is effective in helping the patient control hallucinations. It is hoped that through this research, everyone will understand the importance of psychiatric nursing care, thereby increasing awareness in maintaining and preserving mental health, and implementing behaviors that support optimal mental well-being in everyday life